Hubungan Tingkat Ansietas dengan Siklus Menstruasi pada Mahasiswi S1 Kedokteran Universitas Andalas Tahun 2019 - Lufthi, Alma Sylvhanie; Yaunin, Yaslinda; Aladin, Aladin (Andalas Obstetrics And Gynecology Journal, 2020)
Background: The medical education system is known as a stressful environment that might cause anxiety for the students. Student at the pre-clinical last degree (fourth degree) are also required to do a thesis so that the final year students will had anxiety even though they have adapted to the lecture environment. Anxiety can influence fluctuation Folikel Stimulating Hormone (FSH) and Lutenzing. Hormone (LH) level until the proliferation and secretion process indicate shorten or elongated that cause disruption on the menstruation cycle.Objective: To determine the relationship between anxiety level and menstrual disruption to student the fourth degree at Faculty of Medicine in Andalas University.Method: This research was an observational analytic with a cross-sectional approach. This research was done by a guided interview to 137 female medical students the last degree at Faculty of Medicine in Andalas University. The anxiety level was measured by using the Taylor Minnesota Anxiety Scale (TMAS) questionnaire while the menstrual disruption was acceded by using a menstruation questionnaire.Results: The univariate analysis showed 47.4% of the respondents had a low anxiety level, 19% of the respondents had a middle anxiety level, and 33.6% of the respondents had a serious anxiety level. Meanwhile, the study also showed that 76.6% of the respondents had normal menstrual patterns, while 10.2 % of them were having polymenorrhea. The statistical analysis Chi-square showed p-value was 0.232 (p > 0.05).Conclusion: The conclude that there was no significant relationship between anxiety level and menstrual disruption to student the last degree at Faculty of Medicine in Andalas UniversityKeywords: stress, anxiety level, menstruation disruption